The Role of Farm Households and the Agro-Food Sector in Korean Rural Economy - 허장; 김용렬 (농촌경제, 31(2), 2008)
This paper aims to review the role of farm households and the agro-food sector in the economy of rural areas in Korea. It discusses definition of rural area, share of agricultural and agro-food sectors in Korean economy, the income situation of farm households and non-farming activities, and multiplier effects of agriculture in Korea. Rural areas mean Eup and Myeon, whereas Dong means urban area. Rural population in Korea has continued to decrease over the years. In 2005, 18.3% of total land area, or 1,824thousand ha, was used for paddy and dry fields. The share of GRDP of agricultural, forestry, and fishing sectors was about 10% in 1985, but dropped to slightly over 3% in 2005. Thirty seven percent of farmers have a second employment in the non-farm sector and 67.2% of part-time farmers are more devoted to their non-farm activities than farming for farm household income. Rural tourism provides diverse opportunities for rural and urban residents to exchange products, services, information, and culture. New demands are arising toward rural areas: leisure and relaxation spaces, rural tourism, nature and ecology, rural amenity, and safe and fresh local foods. KCI Citation Count: 1